The 3rd Southeast Asian Conference on Geophysics (SEACG) 2020: Future Challenges and Opportunities in Geophysics (Preface). Issue 1 (October 2021) - Zulfakriza,; Hendriyana, Andri; Saygin, Erdinc; Chhun, Chanmaly
Abstract : The issue of IOP Conference Series: Earth and Environmental Science contains the outstanding papers presented at Southeast Asian Conference on Geophysics (SEACG) 2020. Due to Covid-19 Pandemic, the 3rd SEACG 2020 Conference was held online on 3 – 5 November 2020. List of Committees SEACG 2020, Documetation, Images are available in this pdf.